A Diabetes-Specific Questionnaires Validated in Indonesia: A Systematic Review - Panduwiguna, Ivans; Sauriasari, Rani; Sartika, Ratu Ayu Dewi; Riyadina , Woro (Indonesian Journal of Pharmacy, 2023)
Diabetes is a global problem that is increasingly higher from year to year. Diabetes-specific instruments so far can be well received by patients to evaluate specific aspects of their diabetic disease. This instrument is believed to be one of the best methods to evaluate certain characteristics in diabetic diseases. The purpose of the research is to identify and compare all validated diabetes-specific questionnaires. Researchers performed searches on three different electronic databases: PubMed, ScienceDirect, and Google Scholar. The study was selected covering cross-cultural adaptation and validation methodologies in Indonesia with type 1 and type 2 diabetes patients of all ages. After reviewing the full-text article, data related to psychometric characteristics are extracted from each selected study. Reliability is rated with Cronbach’s (Cα). The initial search identified 1,576 studies. After the exception, 45 studies were put in for review. The questionnaires were grouped into 12 domains based on the focus of the study: adherence (n = 15), quality of life (n = 9), diabetes knowledge (n = 6), self-efficacy (n = 9), Attitude to diabetes (n = 2), emotional stress (n = 8), expectations (n = 1), perception of disease severity (n = 1), risk of developing diabetes (n = 1), family support (n = 3), diet (n = 1) and religiosity (n = 1)This study identifies and reviews all diabetes-specific questionnaires that have been validated for Indonesians to facilitate researchers to select the most appropriate instrument for each domain of interest in future research and clinical settings.